ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL RELASI DAN FUNGSI DI SEKOLAH MENENGAH PERTAMA - Cabita, Aulanda; Haryadi, Rahman; Ardiawan, Yadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze student’s difficulties in solving problems related to relation and function. The research employed a descriptive method with a qualitive approach in the form of a case study. The subjects of this study were 35 ninth-grade students of SMP Negeri 14 Pontianak. Data were collected through essay tests and interviews, then analyzed descriptively to identify the types and causes of students’ learning difficulties. The result showed that students experienced three main types of difficulties. First, conceptual difficulties (40%), indicated by a lack of understanding of the definition of functions, relations, and mathematical symbols. Second, difficulties in applying principles (67%), including errors in determining function formulas, performing calculation, and lack of accurary in solving problems. Third, difficulties in soving verbal problems (40%), reflected in students’ inability to draw function graphs, determine coordinate axes, and understand problem-solving procedures. These difficulties were caused by a lack of conceptual understanding, weak computational skills, and low accuracy in reading and solving problems. Therefore, It is necessary to implement learning strategies that emphasize conceptual undertanding, continuous practice, and improvement of students’ accuracy.